2017
DOI: 10.1123/jsep.2016-0144
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Exploration of the Application of Self-Compassion Within the Context of Sport Injury

Abstract: In a prospective study of collegiate athletes (N = 117), the application of self-compassion within the context of sport injury was explored. Previous literature indicated that self-compassion enhances adaptive coping and well-being and reduces anxiety in stress-provoking situations. This research suggested that it could potentially reduce the stress response and subsequent injury risk. Findings indicated that self-compassion may buffer the experience of somatic anxiety (rs = −.436, p < .01) and worry (rs = −.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
(90 reference statements)
2
18
0
4
Order By: Relevance
“…These results imply that SC can be learned, in turn leading to healthier ways of reacting when confronted with failures and setbacks. In line with these findings, other research shows that SC is associated with less maladaptive coping strategies, namely avoidance focused coping (e.g., behavioral disengagement, denial, or distraction, Barczak & Eklund, 2018;Huysmans & Clement, 2017;Mosewich, Sabiston, et al, 2019). However, in two of these three latter publications, the findings were ambivalent.…”
Section: Athletes' Beliefs About Self-compassionsupporting
confidence: 59%
“…These results imply that SC can be learned, in turn leading to healthier ways of reacting when confronted with failures and setbacks. In line with these findings, other research shows that SC is associated with less maladaptive coping strategies, namely avoidance focused coping (e.g., behavioral disengagement, denial, or distraction, Barczak & Eklund, 2018;Huysmans & Clement, 2017;Mosewich, Sabiston, et al, 2019). However, in two of these three latter publications, the findings were ambivalent.…”
Section: Athletes' Beliefs About Self-compassionsupporting
confidence: 59%
“…Despite our replication of many previous self-compassion findings in other samples (e.g., women athletes, nonathlete samples of men), we were, pragmatically, unable to include all variables that have been previously assessed in self-compassion research. Of note, in recent studies including both men athletes and women athletes, several variables were identified as related to self-compassion (e.g., adaptive coping, subjective well-being, social support, perfectionist strivings, perfectionist concerns, social physique anxiety, sport anxiety; Huysmans & Clement, 2017;Jeon et al, 2016;Koc & Ermis, 2016;Lizmore et al, 2017). Therefore, in future studies on self-compassion and exclusively men athletes, it is important to consider including not only the variables identified as significant in our research but also the entire range of variables that have been previously studied.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the wake of a sole focus on women athletes, there is a recent trend in sport self-compassion research to include both women athletes and men athletes, with encouraging findings (e.g., selfcompassion is positively related to adaptive coping, social support, well-being, and perfectionist strivings, and negatively related to shame and perfectionist concerns; Fontana, Fry, & Cramer, 2017;Huysmans & Clement, 2017;Jeon, Lee, & Kwon, 2016;Lizmore, Dunn, & Dunn, 2017). However, there are few self-compassion studies to date that have focused exclusively on men athletes and the unique challenges that men athletes face in sport, which oftentimes stem from masculinity.…”
mentioning
confidence: 99%
“…Nevertheless, this general focus makes conclusions applicable to the broader population difficult. Our results, along with a small number of other studies (e.g., Huysmans & Clement, 2017;Reis et al, 2019) suggest that men athletes do not appear to be more, or less, self-compassionate, suggesting intervention via this route may be just as warranted.…”
Section: Discussionmentioning
confidence: 39%